Ebba Waaben: Christian 4.s salpeterværker. Udgivet af Kirsten-Elizabeth Høgsbro og Knud Waaben. Studier og kilder, bd. 8. (Rigsarkivet/ G.E.C. Gad, 1995). 228 s., 190kr. - Degn, Ole (Historie/Jyske Samlinger, 1997)
-